Isolation and Characterization of Marine Actinomycetes from West Coast of India for Its Antioxidant Activity and Cytotoxicity - Chidambara Rajan, P (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Characterization of Marine Actinomycetes from West Coast of India for Its Antioxidant Activity and Cytotoxicity